Troubling Tradeoffs in the Human Development Index - Ravallion, Martin (2012)
The 20th Human Development Report has introduced a new version of its famous Human Development Index (HDI). The HDI aggregates country-level attainments in life expectancy, schooling and income per capita. Each year's rankings by the HDI are keenly watched in both rich and poor countries. The main change in the 2010 HDI is that it relaxes its past assumption of perfect substitutability between its three components. However, most users will probably not realize that the new HDI has also greatly reduced its implicit weight on longevity in poor countries, relative to rich ones. A poor country experiencing falling life expectancy due to (say) a collapse in its health-care system could still see its HDI improve with even a small rate of economic growth. By contrast, the new HDI's valuations of the gains from extra schooling seem unreasonably high -- many times greater than the economic returns to schooling. These troubling tradeoffs could have been largely avoided using a different aggregation function for the HDI, while still allowing imperfect substitution. While some difficult value judgments are faced in constructing and assessing the HDI, making its assumed tradeoffs more explicit would be a welcome step.